BUDIDAYA CACING TANAH SEBAGAI SUMBER PAKAN ALTERNATIF DALAM PEMELIHARAAN LELE DUMBO DI PONDOK PESANTREN HIDAYATULLAH, SEMARANG (The Farming of arthworms as an Alternative Feeding of Maintenance Catfish in Hidayatullah Boarding School, Gedawang, Semarang) - Diana Chilmawati; Johanes Hutabarat; Istiyanto Samijan; Pinandoyo Pinandoyo; V. E. Herawati (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2014)
Pemenuhan kebutuhan pakan masih menjadi kendala dalam budidaya lele dumbo di pondok pesantren Hidayatullah Gedawang Semarang. Biaya untuk kebutuhan membeli pakan/pelet tergolong besar. Pemberian pakan cacing tanah (Lumbricus rubellus) sebagai pakan alternatif selain pellet dapat diterapkan untuk mengatasi permasalahan ketersediaan pakan di ponpes tersebut. Sehubungan dengan hal tersebut maka teknologi yang tepat adalah teknologi budidaya pakan alami sebagai pengganti/substitusi pakan buatan. Tujuan Pengabdian Kepada Masyarakat ini adalah untuk mengenalkan dan menerapkan teknologi budidaya cacing tanah (L. rubellus) sebagai pakan alternatif dalam budidaya lele dumbo pada kolam terpal di ponpes Hidayatullah, Desa Gedawang, Banyumanik, Semarang. Hasil pengamatan tentang jumlah kematian benih lele selama kegiatan Pengabdian Kepada Masyarakat ini didapatkan Tingkat Kelulushidupan (Survival Rate/SR) lele dumbo yang dipelihara dengan penerapan pemberian pakan berupa pellet dan cacing tanah, SR nya lebih tinggi (89.83%) dibanding lele yang hanya diberi pakan pellet saja (71.16%). Hasil pertumbuhan lele dumbo yang diberi pakan pellet dan cacing tanah juga menunjukkan lebih tinggi (72 kg) daripada pertumbuhan lele dumbo yang hanya diberi pellet saja (65 kg). Kata Kunci : Cacing tanah (Lumbricus rubellus), pakan alternatif, lele dumbo (Clarias gariepius) Hidayatullah Islamic boarding school, Gedawang Semarang, having catfish farming as an alternative effort to support the school revenue. Feed is a component of fish production which absorbs more than 30% of the cost. This condition is perceived to be quite heavy for a boarding school to keep their fish culture running well. Earthworms (Lumbricus rubellus), can be used as an alternative feeding for the fish, can be applied to overcome the problems of availability on artificial food. Therefore, the application on live food organisms culture technology is the best solution to subtitute artificial feed. Introduction of earthworms cultivations technology is required to solve the procurement artificial feed problem for the fish farming that experienced by Hidayatullah Islamic Boarding Scholl, Gedawang, Semarang. Based on field trials show the result that the survival rate of the catfish that fed with the earthworms reaching 89.83 % after 71 days of culturing. Giving earthworms, can save the needs of artificial diets up to 28.84%. Catfish which fed with combination of pellets and earthworms grow faster with 72 kg in weigh biomass than the fish which only fed with artificial feed (65 kg). Based on these results, it can be concluded that the introduction of appropriate technologies such as earthworms’ cultivations, can reduce the use of artificial feed and increase the growth of African catfish. The use of earthworms feed can reduce feed costs up to 28.84%. Key words : Earthworms (Lumbricus rubellus), alternative feeding, catfish (Clarias gariepius)